PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN GO-JEK - Abdul Malik; Melda Seprianti (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to analyze the influence of service quality and price perception on Go-Jek customer satisfaction simultaneously and partially. Data collection is done by distributing questionnaires and interviews.The research method uses quantitative research.The objects used are FEBI UIN Sulthan Thaha Saifuddin Jambi students with a population of all FEBI UIN Sulthan Thaha Saifuddin Jambi students who use the Go-Jek application more than twice with a sample of 40 respondents.The results showed that the F-test showed that the customer satisfaction variable (Y) could be influenced by the service quality variable (X1) and price perception (X2) together because the sig value was 0.000 <0.05.By t-test service quality (X1) has no effect on customer satisfaction (Y) because the value of sig 0.065> 0.05.Meanwhile, price perception (X2) has a significant effect on customer satisfaction (Y) because the sig value is 0.000 <0.05.